Proinsulin and insulin responses to a mixed meal in hypertriglyceridaemic men. Issue 8 (1st August 1999) - Gama, R; Norris, F; Hampton, S; Morgan, L; Wright, J; Marks, V
Abstract : AIM: To investigate the contribution of proinsulin to the "hyperinsulinaemia" of hypertriglyceridaemia. METHODS: Plasma glucose, triglyceride, immunoreactive insulin, and intact proinsulin concentrations were measured before and after a mixed meal in 11 hypertriglyceridaemic men and six healthy normotriglyceridaemic male controls. RESULTS: Hypertriglyceridaemic subjects had greater fasting (101 v 50 pmol/l) and integrated (139 v 81 x 0(-3) pmol/l/h) insulin concentrations than controls. Fasting and integrated glucose and proinsulin concentrations were similar in the two groups. CONCLUSIONS: Proinsulin does not contribute to the hyperinsulinaemia observed in hypertriglyceridaemic subjects and is therefore unlikely to contribute to the increased cardiovascular risk associated with hypertriglyceridaemia.